Optimal Public Deficit and Tax-smoothing in the Spanish Economy, 1850-2022 - Emilio Congregado; Vicente Esteve García; María A. Prats (London School of Economics and Political Science (LSE), European Institute, 2023)
In this paper we provide a formal test of Barro's tax-smoothing model, using Spanish data covering the period 1850-2022. First, we found that the tax-tilting component has been very important for the Spanish government and is a symptom of the existence of a public deficit bias that has existed in Spanish public finances over the sample period. Second, our empirical findings do also support the existence of tax-smoothing in Spanish fiscal policy throughout the sample period. Consequently, there is some evidence that the Spanish economy has engaged in tax-smoothing behaviour over the period analysed, as the Spanish governments responded to expected future changes in government spending by running budget imbalances, rather than altering contemporaneous government revenues.
Keywords: E62; H21; H62; O52; 330; Optimal taxation; Public debt management; Tax-smoothing; Tax-tilting; Spain